Microbiology of folliculitis: a histological study of 39 cases. Issue 1 (8th May 2013) - Jahns, Anika C.; Lundskog, Bertil; Berg, Johanna; Jonsson, Rebecca; McDowell, Andrew; Patrick, Sheila; Golovleva, Irina; Palmer, Ruth H.; Alexeyev, Oleg A.
<x xml:space="preserve">Abstract</x> Folliculitis is a common inflammatory skin syndrome. Several microbial organisms have been put forward as causative agents, but few studies visualized microbes directly in inflamed hair follicles. This retrospective study investigated bacterial and fungal colonization of inflamed hair follicles in patients with clinically diagnosed non‐infectious folliculitis. Skin biopsies from 39 folliculitis patients and 27 controls were screened by fluorescence in situ hybridization (FISH) using broad‐range bacterial and fungal probes and by immunofluorescence microscopy using a monoclonal antibody towards Gram‐positive bacteria. Specific monoclonal and polyclonal antibodies towards Staphylococcus spp. and Propionibacterium acnes were applied for further species identification. Inflamed follicles were associated with bacterial colonization in 10 samples (26%) and fungal colonization in three samples (8%). Staphylococcus spp. were observed in inflamed follicles in seven samples (18%). Two samples were positive for P. acnes, which were identified as either type II or type IB/type III. Both Staphylococcus spp. and P. acnes were seen in macrocolonies/biofilm structures. In conclusion, one‐third of patients with clinically diagnosed, non‐infectious folliculitis exhibited microbial colonization with predominance of Staphylococcus spp.